ОСОБЛИВОСТІ ЕКСПРЕСІЇ PD-L1 У ТКАНИНІ РЕЦЕПТОР-НЕГАТИВНОГО РАКУ МОЛОЧНОЇ ЗАЛОЗИ - LUKIANOVA, Ye.; MUSHII, O.; KROTEVYCH, M.; ZADVORNYI, T. (PH Akademperiodyka, 2024)
Background. The high heterogeneity and pathogenetic diversity of breast cancer (BCa) indicate the need for further study of tumor cell biology in order to identify molecular biological markers associated with the aggressiveness of tumors with a negative receptor status. Among many factors that may be involved in the initiation and progression of this form of cancer, the study of the immune components of tumor microenvironment, in particular PD-L1, is considered promising. Aim. To investigate the relationship between PD-L1 expression in tumor tissue and clinical and pathological characteristics of BCa, taking into account the status of steroid hormone receptors. Materials and Methods. In tumor tissue of 116 patients with stage I—II BCa, the mRNA levels of CD274 gene were determined using the real-time quantitative polymerase chain reaction. The expression of PD-L1 was studied by the immunohistochemical method. Results. The tissue of receptor-negative BCa was characterized by a significant decrease in the CD274 mRNA level against the background of the increased PD-L1 expression compared to neoplasms positive for the expression of steroid hormone receptors. An inverse correlation was found between PD-L1 at the protein level and the age of patients with receptor-negative BCa (r = –0.613, p = 0.00003). We showed that a characteristic feature of receptor-negative BCa in menopausal patients is the increased expression of PD-L1 both at the protein and mRNA levels (p = 0.005 and p = 0.046, respectively). The correlation of PD-L1 expression with metastatic lesions in regional lymph nodes (p = 0.050), tumor differentiation grade (p = 0.001), and the patient survival rate was revealed. Conclusions. The obtained data indicated the expediency of using PD-L1 expression indicators for in-depth characterization of the tumor microenvironment of receptor-negative BCa, which will allow for the personalized correction of therapy regimens contributing to the improvement of the patients' quality of life.